Enhancing fourth-grade students’ learning outcomes in Tajwīd throughlapbook media: A Classroom action research - Tatik Khalifah; Muhammad Ikhsan Ghofur (AL-TARBIYAH: Jurnal Pendidikan (The Educational Journal), 2025)
This research examine the use of lapbook media as an instructional strategy to enhance fourth-grade students’ achievement in learning tajwīd, specifically the pronunciation rules of nun sākinah and tanwīn. The study was conducted in response to limited student engagement and unsatisfactory learning outcomes commonly found in conventional tajwīd instruction in the primary school level. A Classroom Action Research approach based on the Kemmis and McTaggart framework was implemented through two iterative cycles involving instructional planning, classroom action, observation, and reflective evaluation. The participants consisted of 16 fourth-grade students during the first semester. Data were obtained from achievement tests, classroom observations, interviews, and supporting documentation, and were analyzed descriptively across cycles. The findings reveal a progressive improvement in students’ learning performance, as reflected in the increase of the mean score from 64.37 before the intervention to 75.50 after the first cycle and 88.44 following the second cycle. The proportion of students meeting the mastery criteria also rose from 37.5% to full mastery by the end of the study. Furthermore, classroom observations indicated that lapbook-based activities encouraged greater student participation and learning motivation. These results suggest that lapbook media can be effectively integrated into tajwīd instructionto support active learning and improve educational outcomes in primary education.